Penerapan UI/UX Pada Perancangan Sistem Informasi Penjadwalan Study Case SMK Negeri 2 Kota Tangerang Selatan - Raditya Rimbawan Oprasto; Lily Damayanti (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The User Interface (UI) serves as the design framework guiding user interactions within a system, whereas the User Experience (UX) encompasses the holistic user journey, including activities like data input and report generation. In the context of the scheduling system, the integration of UI/UX is strategically employed to deliver a user-centric experience, emphasizing seamless interaction with system menus. This methodology is expressly designed to optimize usability and cultivate high levels of user satisfaction. This article explores the nuanced interplay between UI and UX within the scheduling system, shedding light on how their collaborative implementation contributes to an enhanced overall user experience. The study delves into the specifics of design strategies aimed at promoting user-friendly interactions, ultimately fostering a positive and efficient user experience.